Bargaining with Incomplete Information: An Infinite-Horizon Model with Two-Sided Uncertainty - Cramton, P. C. (Review of Economic Studies, 1984)
The resolution of any bargaining conflict depends crucially on the relative urgency of the agents to reach agreement and the information each agent has about the others' preferences. This paper explores, within the context of an infinite-horizon bargaining model with two-sided uncertainty, how timing and information affect the rational behaviour of agents when commitment is not possible. Since the bargainers are uncertain about whether trade is desirable, they must communicate some of their private information before an agreement can be reached. This need for learning, due to incomplete information about preferences, results in bargaining inefficiencies: trade often occurs after costly delay. Thus, the model provides an explanation for the inefficient bargaining behaviour that appears to occur often in practice.